NATO “Peacekeeping” Operation in Bosnia and Herzegovina (1992–1995): Concept and Reality - V. I. Bazhukov (Управленческое консультирование, 2018)
In this article the peculiarities of NATO peacekeeping concept, that was created in the course of violent conflict resolution in Bosnia and Herzegovina in 1992–1995 are being reviewed; the methods and factors of the alliance legalization in UN peacekeepingstructures are being analyzed, types of transformation of military bloc from a peacekeeper into a conflicting party are being researched.